Digital health in the management of allergic diseases - Pattini, Stefano; Pingitore, Giuseppe; Cardinale, Fabio; Licari, Amelia; Miraglia Del Giudice, Michele; Calvani, Mauro; Chiappini, Elena; Cravidi, Claudio; Marseglia, Gian Luigi; Ricci, Giampaolo; Duse, Marzia; Tripodi, Salvatore (Acta Biomedica Atenei Parmensis, 2021)
In recent years there has been an important implementation in the medical field of both Mobile Health, such as the use of mobile communication devices, and of other telemedicine tools in general, with the aim of supporting the supervision of diseases from the moment of the first diagnosis to the therapeutic follow-up. In fact, Digital Health can also have a very positive impact on the management of allergic patients, who are known to have the greatest need for regular monitoring, simplifying contact between doctor and patient, but there is still a need to improve implementation regulations, define certification programs and adequate reimbursement systems, as well as to guarantee a high level of attention to the protection of sensitive data. The hope is that one positive outcome of the Covid-19 pandemic will be an acceleration, by all stakeholders involved, of the process of the modernization of health care.